Changes in life skills of top college athletes over four years and its relation to career outcomes - Shimizu, S.; Shimamoto, K.; Kukidome, T.; Tsuchiya, H. (International Journal of Sport & Health Science, 2016)
This research examined the following 2 objectives: one, to clarify the relationship between university athletic activities and the acquisition of life skills (hereinafter called "LS") through a longitudinal study over four years of the top level athletes' university career, and second, to reveal the relationship between LS and career decision after graduation. Longitudinal research, over the course of four years with five survey periods (in April, 2011, 2012, 2013, 2014, in March, 2015) was conducted for 23 top level male wrestlers who enrolled in university in April, 2011 (average age was 18.1±0.3 and years of experience in the sport 6.7±4.0 years at the time of initial investigation). Participants completed the LS evaluation scale (Shimamoto et al., 2013) at all survey periods. Statistical analysis showed that the score of total LS and "thinking carefully," which was considered an important LS from a previous study of male wrestlers increased gradually through top level university athletic activities. In addition, it was suggested that male wrestlers who had a high score of "setting goals" will be able to make career decision upon graduation. Lastly, the effective implementation of Career Development Program for top level male university athletes was discussed based on the results of this research.